Multi-objective constructal design for compound heat dissipation channels in a three-dimensional trapezoidal heat generation body. (October 2021) - Zhang, Zhiming; Feng, Huijun; Chen, Lingen; Ge, Yanlin
Abstract: A three-dimensional compound heat dissipation channel model with both heat conduction and fluid channels in a trapezoidal heat generation body is established in this paper. Firstly, constructal design of the model is conducted by taking the composite function of maximum temperature difference and pumping power consumption as the optimization objective based on the weighted sum method. The optimization results with compound heat dissipation channel and pure fluid channel are compared. Secondly, the Pareto optimal set also obtained by the multi-objective optimization to satisfy different design requirements based on the NSGA-II algorithm. The results show that there exist the optimal fluid channel radius, ratio of trapezoidal height to total length and length ratio of elemental channels to make the composite function of the trapezoidal heat generation body approach its minimum. Compared with the initial design, the composite function is reduced by 25.7% after constructal optimization with three design variables. The result obtained by the weighted sum method is also located at the Pareto optimal set, which simultaneously verifies the results obtained by the weighted sum method and multi-objective optimization method. The optimization results may provide a new theoretical guideline for the designs of various electronic devices.